Examining the relationship between gestational diabetes mellitus and childhood obesity - O'Connor, Carissa; Bégin, Danielle (Université d'Ottawa | University of Ottawa, 2015)
Background: Gestational diabetes mellitus (GDM) occurs during pregnancy, when a woman who was previously not diabetic experiences high blood glucose levels. The prevalence of GDM has increased dramatically since 1984 (Getahun et al., 2008). Studies have suggested a link between GDM and an increased risk in childhood obesity in the mothers offspring. The aim of this literature review was to determine if there was in fact a correlation between GDM and childhood obesity. Methods: Several studies from the body of literature were reviewed to assess the methods and evidence. Search words used included: gestational diabetes, GDM, childhood obesity, epidemiology, birth weight, and intrauterine exposure. The studies found were conducted in different regions around the globe but were primarily conducted in developed countries. Limits included the absence of studies not written in English, the absence of studies in developing countries, and the lack of attention towards women of different ethnic backgrounds. The University of Ottawa library was used to search across many databases at once; searches were not conducted across databases individually. Results: Fourteen studies were reviewed in total. Of the fourteen, 13 indicated a positive correlation, suggesting that GDM is associated with increased BMI and obesity in children. Only 1 study indicated minimal or no correlation. The evidence suggests a potential causal relationship between gestational diabetes mellitus and childhood obesity. Conclusion: These results may pose a concern due to the multiple health risks associated with obesity, such as high blood pressure, type 2 diabetes and cardiovascular disease. Further research may be required to determine various areas of impact of childhood obesity beyond physiological, such as economical, psychological and on public health systems. Another area of potential future study could include more links to what causes GDM, as the literature reviewed seemed divided as to whether it was related to maternal BMI. Primary prevention measures should also be considered.